2016
DOI: 10.1136/bcr-2016-216257
|View full text |Cite
|
Sign up to set email alerts
|

Ileal perforation associated with dengue in the paediatric age group: an uncommon presentation

Abstract: Acute abdomen in dengue, a common arboviral disease found in tropical and subtropical countries, is not uncommon and can occasionally present as acute surgical emergency requiring urgent surgical intervention. The spectrum of acute abdomen presenting as surgical emergency in dengue infection that raises suspicion of an abdominal catastrophe includes acute appendicitis, acute cholecystitis, appendicitis and, rarely, intestinal perforation. All cases of intestinal perforation including appendicular, gastric and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Supplemental Table S5 summarizes the other less common surgical manifestations in dengue. 16,23,[95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110][111][112][113][114] Seven studies and several case reports/series were found mainly from Asian countries. A total of 296 patients were described.…”
Section: Common Causes Of Acute Abdomen In Dengue Infectionsmentioning
confidence: 99%
“…Supplemental Table S5 summarizes the other less common surgical manifestations in dengue. 16,23,[95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110][111][112][113][114] Seven studies and several case reports/series were found mainly from Asian countries. A total of 296 patients were described.…”
Section: Common Causes Of Acute Abdomen In Dengue Infectionsmentioning
confidence: 99%